Effect of abiotic stress on antioxidants in maize - Kellős, Tibor (Acta Biologica Szegediensis, 2008)
Changes in the level of reactive oxygen species and antioxidants were investigated in maize (Zea mays L.) subjected to abiotic stress. Abscisic acid and direct oxidative stress induced an increase in the hydrogen peroxide and lipid peroxide concentrations. The level of the antioxidants examined was increased by nearly all the treatments. The glutathione concentration was higher in the stress-tolerant line Z7 than in the stress-sensitive Penjalinan after treatment with hydrogen peroxide or polyethylene glycol and lower after the application of abscisic acid or NaCl. The activity of glutathione reductase, ascorbate peroxidase, catalase and glutathione S-transferase was greater after almost all the treatments in Z7. A comparison of the antioxidants in two maize lines having different levels of stress tolerance corroborated the importance of the effective removal of reactive oxygen species in defence against abiotic stresses.